Screening and Conjoint Analysis of Key lncRNAs for Milk Fat Metabolism in Dairy Cows - Mu, Tong; Hu, Honghong; Feng, Xiaofang; Ma, Yanfen; Wang, Ying; Liu, Jiamin; Yu, Baojun; Wen, Wan; Zhang, Juan; Gu, Yaling (Frontiers in Genetics, 2022)
Long noncoding RNAs (lncRNAs) play an important regulatory role in various biological processes as a key regulatory factor. However, there are largely unknown for the function and expression profile of lncRNAs in milk fat synthesis of dairy cows. In this study, RNA sequencing (RNA-seq) was used to research the whole genome expression of lncRNAs and mRNA transcripts in bovine mammary epithelial cells (BMECs) of dairy cows with high and low milk fat percentage (MFP), and joint analysis was carried out. We identified a total of 47 differentially expressed genes (DEGs) and 38 differentially expressed lncRNAs (DELs, Padj < 0.05), 11 candidate DEGs that may regulate milk fat metabolism were screened by enrichment analysis. Downregulated differential gene ENPP2 and upregulated differential gene BCAT1 are more likely to participate in the milk fat metabolism, and its function needs further experiments verification. The enrichment analysis of target genes predicted by DELs identified 7 cis (co-localization) and 10 trans (co-expression) candidate target genes related to milk lipid metabolism, corresponding to a total of 18 DELs. Among them, the targeting relationship between long intervening/intergenic noncoding RNA (lincRNA) TCONS_00082721 and FABP4 gene that predicts milk fat metabolism by co-localization and co-expression is worthy of attention. Based on the expression information of DELs, differential microRNAs (miRNAs), and lipid metabolism-related target genes, 156 competing endogenous RNAs (ceRNAs) interaction regulation networks related to milk fat metabolism were constructed. The regulatory network centered on miR-145 will be the focus of subsequent experimental research. The ceRNAs regulatory network related to TCONS_00082721 and TCONS_00172817 are more likely to be involved in milk fat synthesis. These results will provide new ways to understand the complex biology of dairy cow milk fat synthesis and provide valuable information for the breed improvement of Chinese Holstein cattle.